2013
DOI: 10.1139/cjfas-2013-0050
|View full text |Cite
|
Sign up to set email alerts
|

Complex etiologies of emerging diseases in lobsters (Homarus americanus) from Long Island Sound

Abstract: Several diseases have recently emerged in lobsters (Homarus americanus) from Long Island Sound (LIS). Various stressors have been implicated as contributory factors, including increased bottom temperatures, extensive eutrophication with commensurate hypoxia, storm-induced thermal destratification, possible exposures to pesticides and metals, and fishery-induced stressors. Such stressors increase host susceptibility by weakening the host immune defenses and act to increase the transmission and severity of patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 110 publications
1
46
0
Order By: Relevance
“…While predation continues to be cited for the recent declines, other factors such as disease and environmental processes have not been well examined; yet both processes have contributed to declines in other crustacean fisheries (Shields, 2012(Shields, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…While predation continues to be cited for the recent declines, other factors such as disease and environmental processes have not been well examined; yet both processes have contributed to declines in other crustacean fisheries (Shields, 2012(Shields, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…However, a more important biological effect could be the potential decline in egg production, as ESD is more prevalent in ovigerous females. Female lobsters do not normally molt while bearing eggs (Shields and Sainte-Marie 2013), which could lead to death if lesions from ESD are severe, or they may molt prematurely, causing death of the larvae (Kunkel et al 2012). In contrast to these declines in lobster stocks in southern New England waters, studies have suggested an increase in lobster stocks in northern US waters and in LFAs on the east coast of Canada (Howell 2012;Tremblay et al 2013).…”
Section: Mixedmentioning
confidence: 99%
“…For some marine taxa, infectious diseases are increasing in emergence, prevalence, or severity (Ward and Lafferty 2004). In the oceans, many of these diseases are environmental or opportunistic (Burge et al 2013;Shields 2013). Opportunistic diseases occur when environmental stressors weaken the physical and physiological defenses of their hosts (e.g., physical barriers to disease and immune responses), thereby allowing microbes to shift from commensal to pathogenic and potentially causing substantial morbidity or mortality.…”
Section: Introductionmentioning
confidence: 99%